Occupants’ Perception of ‘Healthy Housing’ in High-Density Urban Housing - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (Makara Human Behavior Studies in Asia, 2011)
The quality of housing constitutes the physical condition of housing as well as the perception and actions of the occupants. Assessment of housing quality tends to be based on the physical indicators of the housing environment with less attention to the occupants’ understanding of housing quality. This study explores the housing quality from the point of view of the occupants especially in relation to the concept of ‘healthy housing’. A structured interview was conducted with a number of occupants living in high-density urban housing in order to reveal their understanding of the ‘healthy housing’ concept. The study found the existence of a gap between the occupant’s perception of the healthy housing quality and the factual physical condition of their housing. The occupants tend to evaluate their housing as having good quality, despite the facts found from the observation that some physical requirements of ‘healthy housing’ have not been satisfied yet in most houses. This understanding of ‘healthy housing’ is primarily related to the aspect of cleanliness, while other aspects of healthiness do not seem to get enough attention. These findings become the basis of the discussion on the extent to which the perspective of the occupants should be incorporated in developing programmes for urban housing quality improvement.